EMC aspects in telecommunication buildings struck by lightning - Baker, Abu Md. Ali; Ahmad, Hussein (1999)

(untitled)
The EMC analysis of a telecommunication buildings struck by a direct lightning stroke, based on a simulation model is presented. For this purpose the resulting magnetic and electric fields in the places where the higher susceptible equipment will be installed, has been determined as a function of time considering different lightning struck points. Some illustrations are presented to point out the advantages of the considered EMI prediction model during the design of the electrical and electronic installations, considering lightning effects